2001
DOI: 10.1099/0022-1317-82-5-985
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural proteins 2 and 3 interact to modify host cell membranes during the formation of the arterivirus replication complex

Abstract: The replicase polyproteins of equine arteritis virus (EAV ; family Arteriviridae, order Nidovirales) are processed by three viral proteases to yield 12 non-structural proteins (nsps). The nsp2 and nsp3 cleavage products have previously been found to interact, a property that allows nsp2 to act as a co-factor in the processing of the downstream part of the polyprotein by the nsp4 protease. Remarkably, upon infection of Vero cells, but not of BHK-21 or RK-13 cells, EAV nsp2 is now shown to be subject to an addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
186
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(198 citation statements)
references
References 29 publications
12
186
0
Order By: Relevance
“…For example, the proteins responsible for triggering the formation of membrane structures involved in viral RNA replication, i.e., the viral replication complex, have been pinpointed in such experiments for poliovirus, hepatitis A virus, and members of the nidoviruses (1,14,22,45,46). For HCV, the viral replication complex is not yet characterized.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the proteins responsible for triggering the formation of membrane structures involved in viral RNA replication, i.e., the viral replication complex, have been pinpointed in such experiments for poliovirus, hepatitis A virus, and members of the nidoviruses (1,14,22,45,46). For HCV, the viral replication complex is not yet characterized.…”
Section: Discussionmentioning
confidence: 99%
“…PRRSV type 1 strain LV NSP2 is 861 aa in length while type 2 strains have an additional 100 aa or more, and lactate dehydrogenase-elevating virus and EAV encode NSP2 proteins which are 733 and 401 aa in length, respectively (1,20,36,82,85). Snijder et al (66) found that the NSP2 protein of EAV was involved in proteolysis of replicase precursors and membrane association of the virus replication complex, but no confirming work has been reported for other arteriviruses. Similarity is observed only in the amino-and carboxy-terminal domains among different arteriviruses (14).…”
Section: Amino Acid Alterations In Europrrsv Nsp1␤ and Nsp2mentioning
confidence: 99%
“…4 However, during infection with positive-strand RNA viruses such as poliovirus, [5][6][7] equine encephalitis virus, 8 murine hepatitis virus 9 and SARS virus, 10 mammalian cells accumulate double-membraned vesicles that are thought to serve as platforms for viral RNA replication. In a recent publication in PLoS Biology, 11 we and our co-authors chronicled many similarities between autophagosomes and the vesicles induced by both poliovirus and rhinovirus, including, in addition to their double-membraned structure, induced co-localization of GFP-LC3 and LAMP1, post-fixation staining with monodansylcadaverine 12 and the presence of cytosolic luminal contents.…”
mentioning
confidence: 99%
“…Of potential interest to the autophagy community is the existence of defined viral proteins such as poliovirus proteins 2BC and 3A that can, when expressed together but not separately, induce GFP-LC3 and LAMP1 co-localization and double-membraned vesicles. 7,8,11 Co-localization of viral RNA replication complexes with components of the autophagosome did not demonstrate what the purpose of the co-localization was: do the host autophagosomes facilitate viral replication or help defend against microbial infection? For murine hepatitis virus, it was shown that elimination of Atg5p expression from murine ES cells caused a dramatic reduction in the production of extracellular, enveloped virions, 13 arguing that Atg5p was required in some step of viral production, maturation or cell exit.…”
mentioning
confidence: 99%